Walter Benjamin, Antonio Gramsci and the Problem of Elitist Traditions - Voigt, Frank (International Gramsci Journal, 2023)
The article sheds light on Walter Benjamin’s and Antonio Gramsci’s treatments of elitist traditions. It provides a historical contextualization and brief comparison of the theoretical and political developments of the two contemporaries under this aspect. In the Origin of the German Trauerspiel (1924/25), Benjamin’s historical-philosophical aesthetics are enriched by a history of concepts which increasingly takes up socio-historical aspects. This approach goes beyond Benjamin’s programmatic formulations at the beginning of the 1920s, in which he regarded the work of art as a privileged medium of historical insight that, in theory and method, had to be isolated from history. As for Gramsci, the article elaborates an increasing mediation between social and literary history. This is done, on the one hand, by comparing Gramsci’s statements on Italian Futurism between 1913 and 1922 and, on the other hand, by tracing and examining Gramsci’s criticism of Benedetto Croce’s assessment of the reasons leading to World War I in his History of Europe in the Nineteenth Century (1932) in the Prison Notebooks (Quaderno 10). Despite their differences, the examination of these developments in Benjamin and Gramsci shows three common features in their works of the 1930s: Firstly, both of them change their relation to radical democratic, Jacobin traditions. Secondly, they both display an increasingly historical understanding of concepts of literary intelligence under the aspect of their relationship to the reading public. Thirdly, this understanding led both of them to analyze the rise of fascism in Italy and Germany with regard also to ‘elitist traditions’ in which intellectuals distance themselves from the public for various reasons and motives, but with the consequence that an understanding of their participation in discourses and traditions becomes impossible.